Unlocking financial inclusion for cocoa farmers: catalyzing solar irrigation investment in Ghana - Gbodji, Kekeli Kofi; Quarmine, William; Buisson, Marie-Charlotte; Mitra, Archisman; Schmitter, Petra S.; Muzata, Barbra Sehlule (International Water Management Institute, 2025)
Ghanaian cocoa farmers, who provide livelihoods for over 800,000 households, face significant threats from climate change, including erratic rainfall patterns and droughts lasting up to six months. These conditions jeopardize productivity and income stability. To address this, IWMI conducted research that informed innovative financial models now adopted by Access Bank through the Bridge-In Agric Loan. This loan program leverages IWMI’s financing framework to enable smallholder farmers to invest in solar-powered irrigation systems, fostering resilience against climate change, boosting cocoa yields, and improving economic stability. This brief captures the research process, outlines the Bridge-In Agric Loan’s impact, and offers actionable recommendations to scale the initiative for nationwide benefits.